Predictors of cirrhosis in chronic hepatitis C: Findings from a 24-month follow-up study in Almaty, Kazakhstan - Baimukhanova, Manzura; Kurmanova, Gaukhar; Trimova, Gulzhan; Serikbayeva, Zhanar; Aliftenova, Nazgul; Nurgaliyeva, Bayan; Kazbekova, Assem; Amirtayeva, Shugyla; Sultankulov, Daniyar; Sadykova, Sholpan (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Hepatitis C virus (HCV) infection remains a significant global health challenge, affecting an estimated 50 million people worldwide and causing approximately 1 million new cases annually. The presence of cirrhosis and diabetes mellitus appear to amplify the clinical and economic impact of HCV related disease. This study aims to evaluate the incidence of liver cirrhosis within a 24‑month follow‑up period after HCV diagnosis, as well as its association with diabetes and other prognostic factors. Methods: We performed a retrospective analysis of adults with chronic HCV in Almaty, Kazakhstan, using surveillance and medical record data through December 2024. Eligible patients (ICD‑10 B18.2) had ≥24 months of follow‑up and were assessed for cirrhosis (FibroScan F4) in relation to demographic, clinical, and laboratory factors, including diabetes. Group comparisons and logistic regression identified independent predictors, with statistical significance set at p < 0.05. Results: We performed a retrospective analysis of adults with chronic HCV in Almaty, Kazakhstan, using surveillance and medical record data through December 2024. Eligible patients (ICD‑10 B18.2) had ≥24 months of follow‑up and were assessed for cirrhosis (FibroScan F4) in relation to demographic, clinical, and laboratory factors, including diabetes. Group comparisons and logistic regression identified independent predictors, with statistical significance set at p < 0.05. Conclusions: In patients with chronic HCV in Almaty, Kazakhstan, diabetes, poor glycemic control, elevated GGT, and low platelet count were independent predictors of cirrhosis, while sustained virological response was protective. These findings highlight the need for integrated antiviral and metabolic management, with tailored monitoring for high‑risk patients to reduce disease progression beyond existing dispanserization measures (www.actabiomedica.it)